2006
DOI: 10.1021/es0602593
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives on Perfluorochemical Ecotoxicology:  Inhibition and Induction of an Efflux Transporter in the Marine Mussel, Mytilus californianus

Abstract: The toxicological effects of perfluoroalkyl acids on the p-glycoprotein (p-gp) cellular efflux transporter were investigated using the marine mussel Mytilus californianus as a model system. Four of the perfluoroalkyl acids studied exhibit chemosensitizing behavior, significantly inhibiting p-gp transporter activity. The inhibitory potency is maximal for the longer chain acids perfluorononanoate (PFNA) and perfluorodecanoate (PFDA), with average IC50 values of 4.8 and 7.1 microM, respectively. Results indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 37 publications
2
45
0
Order By: Relevance
“…So far, PFCs have been detected in all environmental and biological matrices, including air, surface and ground water, sediments, arctic ice, soils, birds, polar bears, marine organisms, and even in nonoccupationally exposed individuals (Houde et al 2011). Some PFCs are reported to have adverse effects on plants, animals and humans (Qu et al 2010;Austin et al 2003;Stevenson et al 2006). For example, Qu et al (2010) reported that 10 mgL −1 PFOS treatment could inhibit the elongation and biomass of wheat seedling roots and leaves, and slow the chlorophyll accumulation and soluble protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…So far, PFCs have been detected in all environmental and biological matrices, including air, surface and ground water, sediments, arctic ice, soils, birds, polar bears, marine organisms, and even in nonoccupationally exposed individuals (Houde et al 2011). Some PFCs are reported to have adverse effects on plants, animals and humans (Qu et al 2010;Austin et al 2003;Stevenson et al 2006). For example, Qu et al (2010) reported that 10 mgL −1 PFOS treatment could inhibit the elongation and biomass of wheat seedling roots and leaves, and slow the chlorophyll accumulation and soluble protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Up until now, PFOS and PFOA have been detected in all environmental and biological matrices, including the atmosphere Ahrens et al, 2011;Dreyer et al, 2009), soil (Kim et al, 2015;Wen et al, 2014;Washington et al, 2010), water (Eschauzier et al, 2010;Bossi et al, 2008), sediment (Kwadijk et al, 2010), biota (Houde et al, 2011), and human serum (Gao et al, 2015). Adverse effects of PFOS and PFOA on plants, animals and humans have been reported (Wen et al, 2013;Stevenson et al, 2006). Due to their global distribution, environmental persistence, long distance transportation, and potential accumulation and toxicity, PFASs have been at the center of an increasing number of environmental monitoring studies.…”
mentioning
confidence: 99%
“…Certain contaminants, including PFCs and synthetic musks, have demonstrated the ability to manipulate activity (via inhibition) of transmembrane ATP-dependent efflux pumps, thus potentially increasing contaminant exposure where such efflux transporters contribute to physiological barriers (Lindeman et al 2012). Perhaps the most well-studied of these efflux transporters is the p-glycoprotein (p-gp) which is present in human adrenal, blood-brain and blood-testis barrier, and kidney tissues (Stevenson et al 2006). Study suggests that contaminant inhibition of p-gp action occurs indirectly by a relatively uncharacterised mechanism, rather than direct p-gp binding site saturation (Stevenson et al 2006).…”
Section: General Mechanisms Of Toxicity During Early-life-exposurementioning
confidence: 99%
“…Perhaps the most well-studied of these efflux transporters is the p-glycoprotein (p-gp) which is present in human adrenal, blood-brain and blood-testis barrier, and kidney tissues (Stevenson et al 2006). Study suggests that contaminant inhibition of p-gp action occurs indirectly by a relatively uncharacterised mechanism, rather than direct p-gp binding site saturation (Stevenson et al 2006). Proposed mechanisms include interaction with trans-/integral-membrane proteins and disruption of cellular membrane fluidity leading to increased contaminant permeability (Hu et al 2002;Stevenson et al 2006).…”
Section: General Mechanisms Of Toxicity During Early-life-exposurementioning
confidence: 99%